1993
DOI: 10.1038/clpt.1993.167
|View full text |Cite
|
Sign up to set email alerts
|

Gender-based effects on methylprednisolone pharmacokinetics and pharmacodynamics

Abstract: The pharmacokinetics and selected pharmacodynamic responses to methylprednisolone were investigated in six men and six premenopausal women after a dose of 0.6 mg/kg ideal body weight. Women (luteal phase) exhibited a greater methylprednisolone clearance (0.45 versus 0.29 L/hr/kg) and shorter elimination half-life (1.7 versus 2.6 hours) than men. The volume of distribution of methylprednisolone was similar when normalized for ideal body weight. Pharmacodynamic models were used to examine the methylprednisolone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
100
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(106 citation statements)
references
References 34 publications
5
100
1
Order By: Relevance
“…45 Another feature of this model, the dual cosine function, permitted The lymphocyte pharmacodynamic model used in this study also differed from our previous studies. 2,42,43 In this study, a model that is capable of encompassing a substantial rebound component, as demonstrated by the return of T-helper and T-suppressor lymphocytes beyond corresponding baseline cell counts, was needed. This was accomplished by use of a modified precursor-dependent indirect pharmacodynamic response model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…45 Another feature of this model, the dual cosine function, permitted The lymphocyte pharmacodynamic model used in this study also differed from our previous studies. 2,42,43 In this study, a model that is capable of encompassing a substantial rebound component, as demonstrated by the return of T-helper and T-suppressor lymphocytes beyond corresponding baseline cell counts, was needed. This was accomplished by use of a modified precursor-dependent indirect pharmacodynamic response model.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 7 ml blood samples were drawn into heparin-containing collection tubes at 0, 1,2,3,4,6,8,12,14,16,18,20,24,28, and 32 hours. The blood was centrifuged at 2000 rpm for 15 minutes and the plasma harvested and frozen at −20°C until assayed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…where R m is the mean input rate, R b is the amplitude of the input rate, t z is the peak time (baseline acrophase), and 2/24 converts time into radians (Lew et al, 1993). However, more robust mathematical functions have been developed for cortisol secretion, including a form of Fourier analysis and are the subject of comparison (Chakraborty et al, 1999).…”
Section: Mager Et Almentioning
confidence: 99%